Learning disability and the Scottish Mental Health Act. Issue 2 (6th March 2017) - Welsh, Heather; Morrison, Gary
Abstract : Purpose: The purpose of this paper is to investigate the use of the Mental Health (Care and Treatment) (Scotland) Act 2003 for people with learning disabilities in Scotland, in the context of the recent commitment by the Scottish Government to review the place of learning disability (LD) within the Act. Design/methodology/approach: All current compulsory treatment orders (CTO) including LD as a type of mental disorder were identified and reviewed. Data was collected on duration and type of detention (hospital or community based) for all orders. For those with additional mental illness and/or personality disorder, diagnoses were recorded. For those with LD only, symptoms, severity of LD and treatment were recorded. Findings: In total, 11 per cent of CTOs included LD as a type of mental disorder. The majority of these also included mental illness. The duration of detention for people with LD only was almost double that for those without LD. A variety of mental illness diagnoses were represented, psychotic disorders being the most common (54 per cent). Treatment was broad and multidisciplinary. In all, 87 per cent of people with LD only were prescribed psychotropic medication authorised by CTO. Originality/value: There has been limited research on the use of mental health legislation for people with learning disabilities. This project aids understanding of current practice and will be of interest to readers both in Scotland and further afield. It will inform the review of LD as a type of mental disorder under Scottish mental health law, including consideration of the need for specific legislation.